Resetting histone modifications during human prenatal germline development - Rui Gao; Shiyang Zeng; Dongxu Yang; Xiaocui Li; Wenqiang Liu; Yawei Gao; Dandan Bai; Linfeng Zhang; Chuan Chen; Yunzhe Kang; Beiying Wang; Wei Hong; et al. (Cell Discovery, 2023)
Abstract Histone modifications play critical roles in regulating gene expression and present dynamic changes during early embryo development. However, how they are reprogrammed during human prenatal germline development has not yet been elucidated. Here, we map the genome-wide profiles of three key histone modifications in human primordial germ cells (hPGCs) from weeks 8 to 23 of gestation for the first time by performing ULI-NChIP-seq. Notably, H3K4me3 exhibits a canonical promoter-enriched pattern, though with relatively lower enrichment, and is positively correlated with gene expression in globally hypomethylated hPGCs. In addition, H3K27me3 presents very low enrichment but plays an important role in not only dynamically governing specific bivalent promoters but also impeding complete X chromosome reactivation in female hPGCs. Given the activation effects of both global DNA demethylation and H3K4me3 signals, repressive H3K9me3 and H3K27me3 marks are jointly responsible for the paradoxical regulation of demethylation-resistant regions in hPGCs. Collectively, our results provide a unique roadmap of three core histone modifications during hPGC development, which helps to elucidate the architecture of germ cell reprogramming in an extremely hypomethylated DNA environment.